2017
DOI: 10.1021/acsami.7b06804
|View full text |Cite
|
Sign up to set email alerts
|

Fully Packaged Carbon Nanotube Supercapacitors by Direct Ink Writing on Flexible Substrates

Abstract: The ability to print fully packaged integrated energy storage components (e.g., supercapacitors) is of critical importance for practical applications of printed electronics. Due to the limited variety of printable materials, most studies on printed supercapacitors focus on printing the electrode materials but rarely the full-packaged cell. This work presents for the first time the printing of a fully packaged single-wall carbon nanotube-based supercapacitor with direct ink writing (DIW) technology. Enabled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
111
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(112 citation statements)
references
References 39 publications
1
111
0
Order By: Relevance
“…It is also more likely to cause tip clogging issue due to the carbon‐based material agglomeration. In comparison, the printing resolution of the electrodes in this study is characterized to be 175 ± 25 µm, which is among the best in the recently reported planar carbon‐based energy storage devices fabricated by DIW technique . The superior printability is beneficial from strong shear‐thinning behaviors and moderate viscosities of the inks prepared in this study.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…It is also more likely to cause tip clogging issue due to the carbon‐based material agglomeration. In comparison, the printing resolution of the electrodes in this study is characterized to be 175 ± 25 µm, which is among the best in the recently reported planar carbon‐based energy storage devices fabricated by DIW technique . The superior printability is beneficial from strong shear‐thinning behaviors and moderate viscosities of the inks prepared in this study.…”
mentioning
confidence: 65%
“…The pattern is inspired by conventional supercapacitor interdigital structures, which are suitable for both sensing and wearable energy storage device applications (The dimensions are shown in Figure S2 in the Supporting Information) . The DIW printing resolution of carbon‐based materials in recently reported literature is in the range of 0.5–2.0 mm . To maintain the maximum pristine carbon material properties for high energy performance, many carbon material based inks used in the DIW process are free of binders, which results in poor dispersion of carbon‐based materials in a watery mixture .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using this ink and processing method, interdigitated planar supercapacitor was created with a H 2 SO 4 /poly(vinyl alcohol) gel electrolyte. The supercapacitor has an areal specific capacitance of 1255 ± 74 mF cm −2 at a current density of 4.2 ± 0.8 mA cm −2 , much higher than other supercapacitors prepared via DIW …”
Section: Additive Manufacturing Of Conjugated Polymersmentioning
confidence: 87%
“…The supercapacitor has an areal specific capacitance of 1255 AE 74 mF cm −2 at a current density of 4.2 AE 0.8 mA cm −2 , much higher than other supercapacitors prepared via DIW. [47][48][49] PSS paste with a suitably high initial viscosity and shearthinning behavior is first developed. Utilizing a pneumatic syringe, the authors printed lines of PEDOT:PSS and investigated the influence of two different substrates, glass and a hydrogel made of chitosan and hyaluronic acid, on the electrical properties of the extruded material.…”
Section: D Printing Of Cps Direct Ink Writingmentioning
confidence: 99%